Optimized synthesis of glycyrrhetinic acid-modified chitosan 5-fluorouracil nanoparticles and their characteristics - Cheng M (Dove Medical Press, 2014)
Mingrong Cheng,1,2,* Houxiang Chen,3,* Yong Wang,4,* Hongzhi Xu,5 Bing He,5 Jiang Han,1 Zhiping Zhang1 1Department of General Surgery, 2Department of Endoscopy, Pudong New Area District Zhoupu Hospital, Shanghai, People's Republic of China; 3Zhejiang Huafon Fiber Research Institute, Zhejiang Huafon Spandex Co, Ltd, Wenzhou, People's Republic of China; 4School of Materials Science and Engineering, Wuhan University of Technology, Wuhan, People’s Republic of China; 5Department of General Surgery, Shanghai Fifth People’s Hospital, Fudan University, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: The nanoparticle drug delivery system, which uses natural or synthetic polymeric material as a carrier to deliver drugs to targeted tissues, has a broad prospect for clinical application for its targeting, slow-release, and biodegradable properties. Here, we used chitosan (CTS) and hepatoma cell-specific binding molecule glycyrrhetinic acid to synthesize glycyrrhetinic acid-modified chitosan (GA-CTS). The synthetic product was confirmed by infrared (IR) spectra and hydrogen-1 nuclear magnetic resonance. The GA-CTS/5-fluorouracil (5-FU) nanoparticles were synthesized by combining GA-CTS and 5-FU and conjugating 5-FU onto the GA-CTS nanomaterial. The central composite design was performed to optimize the preparation process as CTS:tripolyphosphate sodium (TPP) weight ratio =5:1, 5-FU:CTS weight ratio =1:1, TPP concentration =0.05% (w/v), and cross-link time =50 minutes. GA-CTS/5-FU nanoparticles had a mean particle size of 193.7 nm, a polydispersity index of 0.003, a zeta potential of +27.4 mV, and a drug loading of 1.56%. The GA-CTS/5-FU nanoparticle had a protective effect on the drug against plasma degrading enzyme, and provided a sustained release system comprising three distinct phases of quick, steady, and slow release. Our study showed that the peak time, half-life time, mean residence time and area under the curve of GA-CTS/5-FU were longer or more than those of the 5-FU group, but the maximum concentration (Cmax) was lower. We demonstrated that the nanoparticles accumulated in the liver and have significantly inhibited tumor growth in an orthotropic liver cancer mouse model. Keywords: liver cancer, targeted therapy, chemotherapy, pharmacokinetics efficacy